2010
DOI: 10.1002/dvdy.22421
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tbx22 during facial and palatal development

Abstract: Mutations in the gene encoding the T-box transcription factor TBX22 cause X-linked cleft palate and ankyloglossia in humans. Here we show that Tbx22 expression during facial and palatal development is regulated by FGF and BMP signaling. Our results demonstrate that FGF8 induces Tbx22 in the early face while BMP4 represses and thus restricts its expression. This regulation is conserved between chicken and mouse, although the Tbx22-expression patterns differ considerably between these two species. We suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 61 publications
(80 reference statements)
1
26
0
Order By: Relevance
“…They also do not normally undergo fusion; instead, avian palatal shelves keratinize before making contact and remain constitutively cleft (Ferguson, 1988). Nevertheless, the expression of several genes involved in palatogenesis is conserved in the chick palatal shelves (Haenig et al, 2002;Fuchs et al, 2010;Sheehan-Rooney et al, 2010), and, as such, the chick is a useful model for studying the regulation of gene expression in the palate. Tgfb3 is not expressed in MEE cells in the chick; when Tgf3 was exogenously added to chick palatal explant cultures, however, fusion of the palatal shelves was observed, indicating that Tgfb3 expression might be a key difference between avian and mammalian palate development (Gato et al, 2002).…”
Section: Palatal Bone Formationmentioning
confidence: 99%
“…They also do not normally undergo fusion; instead, avian palatal shelves keratinize before making contact and remain constitutively cleft (Ferguson, 1988). Nevertheless, the expression of several genes involved in palatogenesis is conserved in the chick palatal shelves (Haenig et al, 2002;Fuchs et al, 2010;Sheehan-Rooney et al, 2010), and, as such, the chick is a useful model for studying the regulation of gene expression in the palate. Tgfb3 is not expressed in MEE cells in the chick; when Tgf3 was exogenously added to chick palatal explant cultures, however, fusion of the palatal shelves was observed, indicating that Tgfb3 expression might be a key difference between avian and mammalian palate development (Gato et al, 2002).…”
Section: Palatal Bone Formationmentioning
confidence: 99%
“…In recent years, a variety of genes contributing to development of the secondary palate have been elucidated [7][8][9][10][11][12][13] . Yet, much remains uncertain regarding the tensor veli palatine muscle, which is known to contribute to the formation of the soft palate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been demonstrated that mesenchymal cells of the developing secondary palate express not only growth factors such as BMP and FGF, but also transcription factors including MSX1, Shox2 and Tbx22 [7][8][9][10][11] . It is further known that the TGF-β signaling pathway contributes to fusion of palatal shelves 12,13) .…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the molecular mechanisms involving Tbx22 in craniofacial development revealed that Tbx22 is regulated by genes, such as Meningioma 1 (Mn1), Fgf8 and Bmp4, that are known to be important for normal palate development Fuchs et al, 2010). Mn1 and Tbx22 have a similar expression pattern during normal palate development and Mn1 directly activates Tbx22 expression in vitro.…”
Section: Tbx22 and X-linked Cleft Palate With Ankyloglossiamentioning
confidence: 99%
“…Taken together, these data indicate that Tbx22 and Mn1 function in the same molecular pathway during palatogenesis. Impaired FGF and bone morphogenetic protein (BMP) signaling can result in cleft palate in humans and mice (Fuchs et al, 2010;Liu et al, 2005;Riley et al, 2007). Tbx22 is induced by Fgf8 and inhibited by Bmp4 signaling (Fuchs et al, 2010).…”
Section: Tbx22 and X-linked Cleft Palate With Ankyloglossiamentioning
confidence: 99%